Nanopore direct RNA sequencing reveals N 6-methyladenosine and polyadenylation landscapes on long non-coding RNAs in Arabidopsis thaliana - Qiaoxia Liang; Jizhou Zhang; Hon-Ming Lam; Ting-Fung Chan (BMC Plant Biology, 2024)
Abstract Background Long non-coding RNAs (lncRNAs) play important roles in various biological processes, including stage development in plants. N 6-methyladenosine (m6A) modification and polyadenylation are noteworthy regulatory processes that impact transcript functions by modulating their abundance. However, the specific landscapes of m6A modification and polyadenylation on lncRNAs remain largely unexplored. The advent of nanopore direct RNA sequencing (DRS) provides unprecedented opportunities for directly detecting m6A modifications and estimating polyadenine (poly[A]) tail lengths on individual RNA molecules. Results Here we utilized nanopore DRS to identify lncRNAs and map the transcriptome-wide m6A modification and polyadenylation landscapes in the model plant Arabidopsis thaliana. Leveraging the Low-abundance Aware Full-length Isoform clusTEr (LAFITE) assembly pipeline, we identified 1149 novel lncRNAs in seventeen nanopore DRS datasets from the wild-type Columbia-0. Through the precise detection of 2381 m6A modification sites on lncRNAs at single-base resolution, we observed that lncRNAs exhibited lower methylation levels compared to protein-coding RNAs, and m6A modification facilitated lncRNA abundance. Additionally, we estimated the poly(A) tail lengths of individual lncRNAs and found that poly(A) tails contributed to lncRNA stability, while their effect was not length-dependent. Furthermore, by comparing lncRNA abundance between 2-week seedlings and 5-week floral buds, we revealed the dynamic expression patterns of lncRNAs during the transition from the vegetative stage to the reproductive stage. These observations provided insights into their potential roles in specific tissues or stages in Arabidopsis, including regulating stage development. Moreover, by integrating information on m6A modification, we unveiled a positive correlation between methylation variances and differential expressions of lncRNAs during stage development. Conclusions These findings highlighted the significance of epigenetic modification and post-transcriptional processing in shaping lncRNA expression and their functions during Arabidopsis stage development, contributing to the growing field of lncRNA research in plants. Clinical trial number Not applicable.